The influence of PJBL-Stem and PBL-based on the learning motivation of the students on the mathematical creative thinking skills - Anna Noviyani; Maison Maison; Syaiful Syaiful (Psychology, Evaluation, and Technology in Educational Research, 2021)
The study aims at (1) identifying the influence of PjBL-STEM and PBL on the mathematical creative thinking skills; (2) the influence of high, moderate, and low learning motivation on the mathematical creative thinking skills; and (3) identifying the interaction between PjBL-STEM & PBL and learning motivation on the mathematical creative thinking skills. The study itself is a Quasi-Experiment Research with Nonequivalent Control Group Design. The samples in the study are 66 Grade VIII students from 24th State Junior High School Batang Hari. These samples are drawn by using the total sampling technique in which the number of the samples is equal to the number of the population. Then, in gathering the data, the methods that have been implemented are observation, questionnaire, and written test. After the data have been gathered, the data are analyzed by using Two-Way ANOVA. Thus, the results of the study show that: (1) PjBL-STEM and PBL influence the mathematical creative thinking skills as having been shown by the significance value 0.000, which is lower than 0.050 (0.000 < 0.050); (2) high, moderate, and low learning motivation influence the mathematical creative thinking skills as having been shown by the significance value 0.000, which is lower than 0.050 (0.000 < 0.050); and (3) there is an interaction between PjBL-STEM & PBL and learning motivation with the mathematical creative thinking skills as having been shown by the significance value 0.030, which is lower than 0.050 (0.030 < 0.050).